Pengaruh Terpaan Akun Instagram @magdaleneid dan Motif Penggunaan Terhadap Persepsi Followers - Wibowo, Devi Aulya; Ahmad Nasher (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2023)
ABSTRACT This study focuses on mass communication's evolution in response to the emergence of new media. Presently, social media has gained unparalleled popularity. As per Hootsuite data, active social media users in Indonesia represent 60.4% of the population, encompassing approximately 167 million users. Remarkably, Instagram alone captures 86.5% of the entire active social media user base in Indonesia. Thus, this research aims to ascertain how exposure to the Instagram account @magdaleneid and its usage motives impact followers' perceptions.The utilized theory is the